NASA: COMMERCIAL PARTNERS ARE MAKING PROGRESS BUT FACE AGGRESSIVE SCHEDULES TO DEMONSTRATE CRITICAL SPACE STATION CARGO TRANSPORT CAPABILITIES - Anon (Journal of Magnetohydrodynamics and Plasma Research, 2011)
After the planned retirement of the space shuttle in 2010, the National Aeronautics and Space Administration (NASA) will face a cargo resupply shortfall for the International Space Station of approximately 40 metric tons between 2010 and 2015. NASA budgeted $500 million in seed money to commercial partners to develop new cargo transport capabilities through its Commercial Orbital Transportation Services (COTS) project. NASA used its other transaction authority to award agreements to commercial partners. These agreements are not federal government contracts, and are therefore generally not subject to federal laws and regulations that apply to federal government contracts. GAO previously reported concerns about whether COTS vehicles would be developed in time to meet the shortfall. Subsequently, GAO was directed by the explanatory statement accompanying the Consolidated Appropriations Act, 2008, to examine NASA's management of the COTS project and its expenditures.